A multilingual and location evaluation of search engines for websites and searched for keywords - AlSobh, Anas; Al Oroud, Ahmed; Al-Kabi, Mohammed N.; AlSmadi, Izzat (Faculdade de Filosofia e Ciências, 2011)
Search engines are competing to be seen as universal, consistent and language independent. In principle, users searching for information through the Internet should get consistent information regardless of the language of the words they are searching for and regardless of the language of the matching or the relevant documents. Nevertheless, the language should affect the sequence or the ranking of the retrieved results. In this project, several tools are built to evaluate words and statements in several languages. Results are evaluated and compared for possible correlation. Another tool is built to crawl websites from different languages and locations in order to measure several aspects of those websites. Results from both studies showed that while it seems that popular search engines are making very good progress toward building search engines that are language and location independent, however, there are some limitations and situations where search for results can be biased toward the popularity of the website language and/or location.